2000
DOI: 10.1007/s000390050012
|View full text |Cite
|
Sign up to set email alerts
|

Embeddings of non-commutative L p -spaces into non-commutative L 1 -spaces, 1 < p < 2

Abstract: It will be shown that for 1 < p < 2 the Schatten p-class is isometrically isomorphic to a subspace of the predual of a von Neumann algebra. Similar results hold for non-commutative L p (N, τ )-spaces defined by a finite trace on a finite von Neumann algebra. The embeddings rely on a suitable notion of p-stable processes in the non-commutative setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2005
2005
2009
2009

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…It remains a prominent question to give a complete generalization of this result to the setting of non-commutative L p -spaces. See, for example, Junge [15].…”
Section: Introduction and Synopsismentioning
confidence: 99%
“…It remains a prominent question to give a complete generalization of this result to the setting of non-commutative L p -spaces. See, for example, Junge [15].…”
Section: Introduction and Synopsismentioning
confidence: 99%
“…There are also results along these lines which deal with the less tractable (commutative) case p > 2, and with certain of the non commutative L p -spaces. See, for example, the papers of Koldobsky and König [17], and Junge [16], respectively. General references on the interplay between p-negative type inequalities and isometric embeddings include Deza and Laurent [8], and Wells and Williams [31].…”
Section: Introduction and Synopsismentioning
confidence: 99%
“…Recent work in this line of research can be found for instance in [13,18,32,35,36]. The recent survey article [29] provides an up-to-date information on the latest developments.…”
Section: Introductionmentioning
confidence: 97%
“…181-215] for more information on this line of research. As in the classical case, the method of the proof in [18] is probabilistic. Theorem 1.1 says a lot more than the classical situation.…”
Section: Introductionmentioning
confidence: 98%